(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article describes the uniqueness of land ownership relations and their types and methods of use in the Kokan khanate. In addition to the types of land properties given in this article, the Kokan khanate also used the forms of ownership, rent, accent, and seclusion.